A 10-week implementation of the FIT FIRST FOR ALL school-based physical activity concept effectively improves cardiorespiratory fitness and body composition in 7–16-year-old schoolchildren - Olsen, Helgi Winther; Sjúrðarson, Tórur; Danielsen, Bára Berghamar; Krustrup, Peter; Larsen, Malte Nejst; Skoradal, May-Britt; Mohr, Magni (Frontiers in Public Health, 2024)
Introduction The purpose of the present study was to investigate the impact of the FIT FIRST FOR ALL school-based physical activity program on health-related physical fitness in Faroese schoolchildren. The program aimed to add three weekly sessions of organized high-intensity physical activity to the standard weekly physical education sessions for all pupils across the entire school. Methods A non-randomized controlled design was used to evaluate the effects of the program. Two schools participated, including one intervention school (INT; n =179) and one control school (CON; n =181), with pupils aged 7–16 years (grades 1–9). The FIT FIRST FOR ALL program consisted of three weekly 40-minute sessions of age-adjusted high-intensity physical activity over 10 weeks for the INT school, while the CON school continued their normal school program. Pre- and post-intervention assessments included cardiorespiratory fitness (Yo-Yo IR1C test), agility (Arrowhead Agility test), postural balance (Stork Stand), standing long jump performance, body composition, blood pressure, and resting heart rate. Results A significant time × group effect (p < 0.001) was observed for cardiorespiratory fitness, which increased by 31% [23;39] in INT (p < 0.001) and remained unaltered in CON (7% [−2;16], p = 0.13). In addition, a time × group effect (p < 0.001) was observed for agility, which improved by 2.1% [1.0;3.2] in INT (p < 0.001) and regressed by 3.3% [2.3;4.4] in CON (p < 0.001). No significant between-group effects were found for standing long jump and balance. A time × group effect (p < 0.001) was observed for changes in total muscle mass, which increased by 1.4 kg [1.2;1.5] in INT (p < 0.001) and by 0.4 kg [0.3;0.6] in CON (p < 0.05). Furthermore, a time × group effect (p < 0.001) was observed for total fat percentage, which decreased by −2.3% [−2.8;−1.9] in INT (p < 0.001) and remained unchanged in CON (−0.3% [−0.7;0.1], p = 0.16). No significant time × group effects were found for blood pressure and resting heart rate. Discussion The FIT FIRST FOR ALL program significantly improved cardiorespiratory fitness and agility, and it led to favorable changes in body composition in the intervention school. These findings suggest that the program is highly effective in enhancing physical fitness and health status across all investigated age groups when implemented at a school-wide level.